PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DILENGKAPI LKS UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS VII5 SMP NEGERI 14 PADANG - Siregar, Titik Ermila; Fauzan, Ahmad; Ahda, Yuni (Kolaboratif, 2014)
The learning process in class VII5 of SMP Negeri 14 Padang was not able to create a condition as it was expected yet. The student’ activities in asking questions, answering questions, taking note on the learning materials, paying attention to the teacher’s explanation, discussing, presenting, expressing ideas and completing the Student Worksheet as well as their achievement in learning were still low. This research was designed for describing the improvement of the students’ activities and Biology learning achievement through the use of Think Pair Share cooperative learning model accompanied with Student Worksheet in class VII5 of SMP Negeri 14 Padang. This is a classroom action research. The subject of the research is the student in class VII5 of SMP Negeri 14 Padang registered in Academic Year 2013/2014 that consisted of 32 people. This research was conducted reflecting. The Instruments of the research were observation sheet and the students’ learning achievement. The data was colled through observation and learning achievement test. The data of the research was analyzed qualitatively and quantitatively. The result of the research indicated thet the use of Thin Pair Share cooperative learning model accompanied with Student Worksheet could improve the student learning activities in which the student’average score in the first cycle was 70,33% and in the second cycle was 91,8%. In addition, making use of Think  Pair Share cooperative learning model accompanied with Student Worksheet could improve the students learning achievement in which the students’ average score in the first cycle was 74,19% and in the second cycle was 86,6%. Based on these results, it was concluded that there was an improvement on the student’ activities and learning achievement in class VII5 of SMP Negeri 14 Padang after Think Pair Share cooperative learning model accompanied with Student Worksheet applied. Keyword: Cooperatif learning model, Think Pair Share, Student Worksheet.